Upaya Meningkatkan Kemampuan Bahasa Inggris Anak Usia Dini Melalui Metode Bercerita Gambar Seri Kelompok B di TK Aisiyah Sambon Tahun Ajaran 2016/2017 - Tri Hastutik, Whinda; , Sri Slamet, S.Pd, M.Hum, M.Pd (2017)
Whinda Tri Hastutik/ A520130046. The effort to enhance English skill for early child through telling series picture story of group B at Aisyah kindergarten in Sambon 2016/2017 academic year. Research paper. Teacher Training and Education. Faculty Universitas Muhammadiyah. March, 2017. This research aims to know the increasing English skill for early child story of group B at Aisyah kindergarten in Sambon in the academic year 2016/2017 through telling series picture story. This research is classroom action research (CAR). The subject of this research was early student of group B age 5-6 years old at Banyudono Boyolali. The action research was held at two cycles in five meetings. There were four steps of analyzing data technique, namely planing, acting , observation or monitoring, and analysis and also reflection. The data of early student's English skill and the process of teaching learning with series picture was collected by observation, interview, and field notes. This research used triangulation by looking for the data from any sources. Based on the result of cycle one and two which have held, it showed that there was the development of English skill on early child of group B at Aisyah kindergarten in Sambon. Before doing the cycle of the research, there is student's result which gains good level. Cycle one had got 55% and cycle two had got 70%. This research can be drawn that by applying series picture method can enhance early child's English skill of group b at kindergarten Aisyah in Sambon in the academic year 2016/2017.